The Impact of Tariffs on a Transnational Supply Chain under Different Power Structures in China - Zongbao Zou; Lihao Chen; Yuxin Liang (Mathematics)
In the trade environment of a globalized economy, tariffs play a crucial role in transnational supply chains. At the same time, the power structure of the supply chain also plays an important role in the decision making and income distribution of a transnational supply chain. Therefore, we construct game-theoretic models to analyze the impacts of tariffs and power structures on the decision making and revenue distribution of transnational supply chains. First, we consider a bilateral monopoly model consisting of a Chinese manufacturer and a U.S. retailer and analyze the effects of tariffs and power structures on decision making and revenue distributions in this supply chain. Then, we extend the model to a duopoly competition model consisting of two Chinese manufacturers and one American retailer, further analyzing the roles of tariffs and power structures. The results indicate that in the bilateral monopoly model, the impact of tariffs on the manufacturer’s profits is always greater than on the retailer’s profits under a manufacturer-led circumstance. However, in a competitive model, when the market size is large, the impact of tariffs on the manufacturer’s profits exceeds that of the retailer’s profits; conversely, when the market size is smaller, the impact of tariffs on the retailer’s profits is greater than on the manufacturer’s profits. Furthermore, we find that in the duopoly competition model, under the manufacturer-led circumstance, both the manufacturer and the retailer earn the highest profits.